DIGITAL DA’WAH: EASURING THE QUALITY OF DA'I IN USTADZ MEDIA PHENOMENON AND RADICALISM OF DA'I - Ahmad Hayyan Najikh (Indonesian Journal of Islamic Communication, 2022)
Religion and radicalism are two things that have always been associated recently. Especially Islam which often becomes a religion that produces a lot of radical actions or movements. Moreover, it is supported by the excitement in cyberspace with the existence of information that included 180 names of radical da’i in social media. The excitement experienced by netizens is not only about the information, but also regarding the names of da’i who often decorate TV and social media. In this research, the researcher wants to examine the quality of da’i in digital da'wah amidst the rise of the phenomenon of media da’i and radical da’i and how to respond da'wah in digital era which provides convenience but has its own impact. The results of this study are: first, the implementation of da’wah in millennial era should adapt to the materials, methods and media that are familiar to the society. Second, da’wah approach is no longer enough with the conventional way, but by maximizing the media that is trending around society. Third, in the midst of using technological media as medium of da’wah, it needs to be an inculcation of understanding of religion as a guide, a way of life and human rules. Social media must present a content that is polite and tolerant based on the Islamic concept of Rahmatan Lil Alamin.